3022 [videorecording (DVD)] - Epps, Omar; Walsh, Kate, 1967-; Cosgrove, Miranda, 1993- (Paramount Home Entertainment, 2020)
Halfway through a ten-year mission, a group of astronauts becomes unstable, overcome by the isolation of deep space. While they prepare to return home, Earth is hit by a catastrophic event. The haunting emptiness of space becomes the least of their concerns as they fight to survive against unforeseen threats.